Retrospective analysis of smaller than 3-cm umbilical hernia repair with the lightweight macroporous mesh. Issue 36 (September 2018) - Xie, Yanyan; Song, Yinghan; Ma, Dongyang; Jian, Fushun; Zhang, Sen; Lu, Anqing; Wang, Yong; Lei, Wenzhang
Abstract : Abstract: There is evidence that mesh repair for primary umbilical hernias results in fewer recurrences and similar wound complication rates compared to tissue repair. Various devices and surgical approaches are used in umbilical hernia repair. The ULTRAPRO PLUG (UPP) has been adopted for inguinal hernias and femoral hernias with excellent results. However, there are few reports on the use of UPP for umbilical hernia repair. Thus, the aim of this study was to evaluate efficacy and safety in the treatment of smaller than 3-cm umbilical hernias using the UPP. The medical records of 123 patients who underwent umbilical hernia repair using the UPP between October 2011 and September 2017 were reviewed. All patients were followed-up after 1 month and later in 2018. Demographics, surgical information, and immediate postoperative and long-term complications were assessed. Out of 123 patients, there were 37 male and 86 female patients with a mean age of 50.6 years. The median duration of hernia surgery was 20.5 min (range, 12–34), and 109 (88.6%) patients underwent day surgery. The median defect diameter was 1.4 cm (range, 0.5–3). No mortality or major complications occurred during the perioperative period. Long-term follow-up data were available for 107 (87.0%) patients. The median follow-up duration was 33 months (range, 5–76 months). Early postoperative complications included 1 case of seroma, 2 cases of fat liquefaction, and 1 case of superficial surgical site infection. During follow-up, there were 2 recurrences, 1 case of chronic mesh infection, and 2 patients with chronic postoperative pain. The ULTRAPRO PLUG offers a simple and quick means of repairing smaller than 3-cm umbilical hernias with lower recurrence rates and fewer postoperative complications.